THE IDEATIONAL MEANING IN THE U.S. PRESIDENTIAL DEBATE BETWEEN BARACK OBAMA AND MITT ROMNEY CONCERNING CHINA’S THREAT (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This article deals with ideational meaning realized in transcript of the U.S. presidential debate between Barack Obama and Mitt Romney concerning China’s threat. Ideational meaning talks about subject matter. It relates to information about objects or to what the utterances are about. In realizing the subject matter of the debate transcript, three analyses are conducted; Transitivity, speech function, and also analysis on context of situation. The result based on those analyses shows two points of conclusion. Firstly, Obama through Material and Relational Processes stated his past actions and recent U.S. condition to show his success and through Mental Process he certainly stated his hopes for the future. Meanwhile, Romney through Material and Relational Processes certainly stated the unfortunate condition experienced by the U.S. as a result of Obama’s policies and through Mental Process stated his wish to the U.S economy. Both speakers invited the audiences to accept the information concerning those solutions. Secondly, context of situation influences the debate transcript in its language use. Some terminologies in the area of economy and trade emerge as the influence of Field. Those terminologies make the conversation focuses on the subject matter being analyzed, that is China as a threat to the U.S.